Economic Approach for Synthesis of Gold Nanoparticle-based Freeze Indicator for Fish Products - Sreelakshmi, K. R.; Mohan, C. O.; Renjith, R. K. (International Journal of Bio-resource and Stress Management, 2024)
This study was conducted during the period September 2020–January 2023 at ICAR-Central Institute of Fisheries Technology, Cochin. The study was to develop a cost-effective freeze indicator using gold nanoparticles. Gold nanoparticles (AuNPs) were synthesized using chitosan and trisodium citrate (TSC) as a reducing agent. Various chitosan samples with different molecular weights were obtained from commercial chitosan units. Chitosan was employed at two distinct concentrations. The UV-Vis spectra exhibited the characteristic peak of AuNPs at 520–530 nm in all analyzed samples. The samples containing chitosan displayed a light pink color, whereas those containing TSC exhibited a ruby red color. An increase in chitosan concentration led to an increase in absorbance of the SPR peak. The full width at half maximum (FWHM), zeta potential, and conductivity of the nanoparticles were also investigated. The stability of the synthesized nanoparticles was assessed during frozen storage at -18°C, revealing that the sample containing TSC became colorless upon freezing. The stability of chitosan-containing samples improved with higher concentrations and molecular weights. No distinct color change upon freezing was observed in the samples synthesized using chitosan. The AuNPs synthesized using TSC were evaluated and the significant color change demonstrated by the sample confirmed that the nanoparticle solution synthesized using TSC at a gold concentration of 1 mM can serve as an effective freeze indicator for food and pharmaceutical applications.